Effect of speech therapy on quality of life in patients with spinocerebelar ataxia type 3 - Giovana Diaféria; Silvana Bommarito; Pedro Braga Neto; Sung Woo Park; Marina Padovani; Fernanda Haddad; Leonardo Haddad; Mariana Callil Voos; Hsin Fen Chien; José Luiz Pedroso; Orlando Barsottini (Arquivos de Neuro-Psiquiatria)
Background Individuals with spinocerebellar ataxia type 3 (SCA3) present communication and swallowing disorders, and consequent deterioration in quality of life (QOL). Objective To evaluate the impact of a speech therapy rehabilitation program on the QOL of patients with SCA3. Methods All participants were randomly assigned to two groups, an intervention group receiving speech therapy (STG) and a control group (CG). The International Cooperative Ataxia Rating Scale scores were 32.4 ± 20.2, and the Scale for the Assessment and Rating of Ataxia scores were 11.8 ± 8.0. The intervention consisted of a 12-session speech therapy rehabilitation program with oral, pharyngeal, and laryngeal strengthening exercises—the so-called ATAXIA–Myofunctional Orofacial and Vocal Therapy (A-MOVT). They all were submitted to pre- and postintervention evaluations using the World Health Organization's Quality of Life (WHOQOL-BREF) assessment, as well as the Living with Dysarthria (LwD), Quality of Life in Swallowing Disorders (SWAL-QOL), and Food Assessment Tool (EAT-10). Results The study sample consisted of 48 patients with SCA3 (STG = 25; CG = 23), mean age was 47.1 ± 11.4 years; mean age at symptom onset was 36.9 ± 11.3 years; disease duration was 11.9 ± 13.3 years. After the 3-month intervention, there were significant changes in the QOL in the STG compared with the CG, when assessed by the LwD (179.12 ± 62.55 vs. 129.88 ± 51.42, p < 0.001), SWAL-QOL (869.43 ± 153.63 vs. 911.60 ± 130.90, p = 0.010), and EAT-10 (5.16 ± 7.55 vs. 2.08 ± 3.85, p = 0.018). Conclusions Patients with SCA3 should receive continuous speech therapy as part of the A-MOVT program, because therapy helps to improve difficulty swallowing and dysarthria.